Trade and Economic Growth : Evidence on the Role of Complementarities for CAFTA-DR Countries - Calderón, César (2012)
This paper examines the effects of trade on growth among Central America-Dominican Republic Free Trade Agreement countries. To accomplish this task, the authors collected a panel data set of 136 countries over 1960-2010, and estimated cross-country growth regressions using an econometric methodology that accounts for unobserved effects and the likely endogeneity of the growth determinants. Following recent empirical efforts, they tested whether the impact of trade openness on growth may be more effective after surpassing a "minimum threshold" in specific areas closely related to economic development. The analysis finds not only that there is a robust causal link from trade to growth, but also that the growth benefits from trade are larger in countries with higher levels of education and innovation, deeper financial markets, a stronger institutional framework, more developed infrastructure networks, a high level of integration with world capital markets, and less stringent economic regulations. On average, rising trade has benefited growth in Central America-Dominican Republic Free Trade Agreement countries. However, the lack of progress in structural reforms has not allowed these countries to maximize the potential benefits from trade.